Cuidado de enfermería en paciente de 60 años con úlceras flebostaticas con infección por pseudomonas aeruginosa en extremidades inferiores. - Campuzano Olvera, Samantha Elizabeth (2023)
Phlebostatic ulcers occur most frequently on the lower limbs and are lesions that cause continuous skin damage. They are vascular in nature, resulting from a worsening of cutaneous blood microcirculation induced by arterial or venous insufficiency (Anguita, 2021).Between 10 and 35% of people suffer from some form of chronic venous disease which is one of the most serious complications, ranging from spider veins to simple varicose veins or venous ulcers. This disease affects around 4% of people over 65 years of age (Anguita, 2021).They influence the patient's lifestyle, as well as healthcare costs. Since there is no single therapy for them, the patient receives a combination of therapies. Despite technical advances in ulcer care, as well as a wide range of therapies that combine the latest and the oldest, phlebostatic ulcers are difficult to cure and have a high recurrence rate (Sosa Vázquez, Úlceras flebostáticas, 2017).The research objective is to use tools such as the nursing care process in the care, treatment and promotion of the need for continued pharmaceutical therapy for the management of phlebostatic ulcer. As a consequence of the patient's great outcome, nursing care was provided, completing all objectives and allowing the patient to be discharged home.